2020
DOI: 10.1016/j.annonc.2020.08.1145
|View full text |Cite
|
Sign up to set email alerts
|

1025MO First-in-human (FIH) phase I study of RO7122290 (RO), a novel FAP-targeted 4-1BB agonist, administered as single agent and in combination with atezolizumab (ATZ) to patients with advanced solid tumours

Abstract: Conclusions: FP-1305 administration in advanced cancer patients can promote immune switch and peripheral lymphocyte activation alongside promising tolerability. Despite relatively short half-life, durable Th1 activation and mobilization of NK and B cells accompanied with persistent IFNg and CXCL10 induction was observed. Despite formal progression according to RECIST, potential anti-tumour activity was noted with some target lesions showing regression or stability in several patients. Targeting Clever-1 holds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The bispecific antibody targeting FAP/4-1BB enhanced T-cell stimulation in vivo and led to tumor remission in mouse models ( 106 ). An ongoing phase I trial is currently testing RO7122290 in monotherapy or in combination with atezolizumab in patients with advanced solid tumors ( 107 ).…”
Section: Immunosuppression In Ovarian Cancermentioning
confidence: 99%
“…The bispecific antibody targeting FAP/4-1BB enhanced T-cell stimulation in vivo and led to tumor remission in mouse models ( 106 ). An ongoing phase I trial is currently testing RO7122290 in monotherapy or in combination with atezolizumab in patients with advanced solid tumors ( 107 ).…”
Section: Immunosuppression In Ovarian Cancermentioning
confidence: 99%
“…Clinical response as monotherapy was limited and likewise did not appear promising when combined with atezolizumab. It is uncertain whether anti-drug antibodies (ADAs) may have negatively impacted efficacy because ADA in 20% of the evaluable patients with loss of efficacy in 40% of the positive patients was reported [ 80 ]. RO7227166 is also being investigated in a phase I study.…”
Section: Technological Advances To Mitigate Hepatotoxicity For Cd137 Targeting Moleculesmentioning
confidence: 99%
“…CD137 targeting bispecific molecules are attractive agents with less safety concerns for CRS than CD3 targeting bispecific molecules and may be able to provide prolonged efficacy of T cell activation even a TAA is lost. Previous clinical studies of HPN424 and RO7122290 showed the potential of combination studies with PD-L1 inhibitors [ 75 , 80 ]. Utomilumab in combination with pembrolizumab was assessed in 33 patients with solid tumors and the combination achieved a 26% ORR including 1 CR, however, the effect of the combination compared with pembrolizumab monotherapy is unclear [ 60 ].…”
Section: Potential Combination Partners For Cd137 Targeting Moleculesmentioning
confidence: 99%
“…More recent strategies are focused on bispecific approaches aimed at promoting tumor-target mediated clustering of CD137 to limit systemic and liver toxicities [9][10][11] and early patient data shows encouraging evidence of safety and clinical benefit with correlative pharmacodynamics. 12 13 We recently reported that fully synthetic bicyclic peptides (Bicycles), discovered via phage display and optimized using structuredriven design and medicinal chemistry, can be used as building blocks to create novel synthetic immune agonists. These Bicycle tumor-targeted immune cell agonists (Bicycle TICAs) could achieve clustering and activation of CD137 using a highly expressed tumor Open access antigen to provide a scaffolding function to oligomerize the CD137 Bicycle presented to immune cells.…”
Section: Background Cd137 (4-1bb/tnfrsf9mentioning
confidence: 99%